Radio Frequency Identification for efficient Library Management - Khairul Azizan, Suda; Nazatul Shima, Abdul Rani (2013)
Auto identification and data collection technology is known as radio frequency identification (RFID) helps to automate business processes and allow identification of large number of tagged objects such as books by means of radio waves. It is used in supply chain management in tracking the movement of inventories, equipments, devices and others. Most libraries automate the tracking of books and documents by utilizing the RFID technology in managing the movements of books from shelves and others. This paper is highlighting the application, requirements, benefits, challenges and other issues by incorporating RFID in university/institution library management. Key Words: supply chain management, radio frequency identification, library management system, books.